Performance analysis of PVSyst based grid connected photovoltaic systems in Pakistan compared to SAARC countries - Khan, Muhammad Muneeb; Ahmad, Sadiq; Raza, Ali; Sikandar, Haroon; Hassan, Rana Gulraiz; Shafi, Muhammad Amir (Mehran University research journal of engineering and technology, 2024)
Electricity demand increasing day by day with the passage of time, fossil fuels and traditional electricity sources are becoming obsolete. The possibility of dealing with a power deficit and importing oil and gas for electricity generation exists for developing nations like Pakistan. One of the most accessible and affordable sources of renewable energy in the world is solar power generating. Photovoltaic (PV) cell performance is influenced by the environment and the technology used to capture the available energy. The Islamabad region of Pakistan is blessed with an average of 300 days of sunshine a year due to its location in the solar band at 33.7215°N latitude and 73.0433°E longitude. The current study compares and contrasts how Pakistan and South Asian Association for Regional Cooperation (SAARC) countries generate electricity using solar systems. Choosing one geographical place from all SAARC nations, PVSyst software is used to develop and estimate the performance study for solar model cell Panasonic 320Wp, 48V and 1.5 kW Inverter Fronius for a 9.6 kWp load.  Energy supplied into the grid is studied together with various losses that occur in the system, with the choice of PV arrays and other factors remaining the same for comparison study of all SAARC countries. The approach to minimize losses through the utilization of an adjustable tilt angle has been implemented. This study will be useful in estimating and planning the solar energy output in all SAARC nations for the same photovoltaic system, and it will be simple to trade all PV system components in the region.